Diet, Cooking and Cosmology - Interpreting the Evidence from Bronze Age Plant Macro fossils - Skoglund, Peter (Current Swedish Archaeology, 1999)
The aim of the article is to discuss how the composition of Bronze Age macrofossil samples reflects different aspects of daily life like diet and cooking. The article argues that the increasing weed content in the Late Bronze Age macrofossil samples should partly be regarded as a new resource that was used in the cooking process. The contemporaneous increase in hulled barley at the expense of naked barley and wheat, might reflect a diminished interest in baking leavened bread and a stronger preference for cooked cereal-based dishes. These changes in the domestic sphere should be regarded as intimately connected with changes in the Late Bronze Age cosmology, in particular with the development of the Urnfield culture.